How much N2 is fixed by perennial clovers in Mediterranean sown pastures? - Thanopoulos R.; Ledgard S.F. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
This study investigated N2 fixation by perennial clovers in an area of the Mediterranean basin (Ioannina, N.W. Greece). Pasture treatments were white clover (Trifolium repens) or red clover (Trifolium pratense) sown in binary mixtures with perennial ryegrass (Lolium perenne) and perennial ryegrass in monoculture. Production during two years after sowing was highest in red clover pastures and the yield of red clover was 2-6x that of white clover. N2 fixation was measured using the 15N dilution technique. The amount of N fixed in above ground tissues of white and red clover was 88 and 265 kg N ha-1 respectively, in the establishment year and 37-104 and 78-214 kg N ha-1 in the first productive year. N2 fixed by the clovers will be an important N source for the associated non-legume species via transfer.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)